Research on Ultra-Wideband Radar Life Detection Algorithm Based on SE and SSD - Xin, Li; Jing, Zhou; Zhen, Yang; Jiayi, Li; Wenchen, Jiang (IEEE sensors journal, 2023)
Using pulsed ultra-wideband (UWB) radar noncontact detection technology, when detecting vital sign signals, the weak vital sign echo signals are often covered by various noises, resulting in the inability to identify and locate human targets. To solve this problem, an UWB radar life detection algorithm based on the combination of sample entropy (SE) and singular spectrum decomposition (SSD) is proposed. The human target position information is determined according to the SE value of the radar received pulse. In addition, the respiration and heart rate information were obtained using the SSD method. Fifteen groups of experiments were carried out, and the echo radar signals of five volunteers at three distances were collected, respectively. The measured data analysis results show that the proposed algorithm can accurately and effectively extract the distance and vital signs information of human targets and has extensive research value and application prospects.